Kontribusi Kader Posyandu dalam Intervensi Stunting: Kajian Literatur Tahun 2023–2025 - Aulia, Fita Oktaviani; Dewi Purnamawati (Penerbit Goodwood, 2025)
Purpose: This research aims to examine how empowering Posyandu cadres through training in health status monitoring and nutrition counseling can contribute to reducing stunting rates among toddlers in Indonesia. Methodology/Approach: The study adopts a systematic literature review method, analyzing 35 relevant sources published between 2023 and 2025. The literature includes indexed journal articles, community service reports, government policy documents, theses, and dissertations. Databases such as Google Scholar, PubMed, DOAJ, SINTA, and Garuda Ristekbrin were used with keyword combinations like